Nosocomial SARS‐CoV‐2 infection in urology departments: Results of a prospective multicentric study. (13th October 2020) - Sánchez, María Dolores; Sánchez, Miguel; De La Morena, José Manuel; Ogaya‐Pinies, Gabriel; Mateo, Erika; Moscatiello, Pietro; Sánchez, Susana; Rubio, Victor; Bueno, Carolina; Barba, Raquel; Carracedo, David
Abstract : Objective: To evaluate the coronavirus disease 2019 perioperative infection rate and mortality rate of patients undergoing urological surgeries during the early pandemic period in Spain. Methods: This was a non‐interventional multicenter prospective study carried out from 9 March to 3 May 2020 in two urology departments in Madrid, Spain. Clinical, microbiological and radiological data of patients who underwent surgery were collected from computerized medical records. Results: A total of 148 patients were included in the study, and 141 were analyzed for nosocomial infection risk, after excluding previous and concomitant severe acute respiratory syndrome coronavirus type 2 infections. Elective surgeries represented 76.6% of the procedures, whereas emergent surgeries represented 23.4%. Preoperative screening was carried out with polymerase chain reaction test in 34 patients, all were negative. A total of 14 patients also had chest X‐ray (not suspicious in all cases). Three patients (2.1%) developed severe acute respiratory syndrome coronavirus type 2 nosocomial infection (symptoms developed between the third day after surgery to the 14th day after hospital discharge). Time from admission to a compatible clinical case was 5.5 days (4–12 days). Two patients underwent surgery with concomitant diagnosis of coronavirus disease. The mortality rate due to severe acute respiratory syndrome coronavirus type 2 infection is 0.7%, and the specific mortality rate in patients undergoing surgery with community‐acquired coronavirus disease 2019 infection was 50% (1/2). Conclusions: The nosocomial severe acute respiratory syndrome coronavirus type 2 infection rate was low in patients undergoing urological surgical procedures during the peak of the pandemic in Madrid. With appropriate perioperative screening, urological surgical activity can be carried out in safety conditions.